Body talk : Feminism, Sexuality and the body in the work of Six African Women Artists - Kouoh, Koyo; Barois De Caevel, Eva; Sebti, Alya; Adams, Sarah; Ekotto, Frieda (Brussels : Wiels, 2015)
Bouabdellah, Zoulikha; Kure, Marcia; Syowia Kyambi, Miriam; Oka, Valérie; Rose, Tracey; Zangewa, Billie
Body Talk: Feminism, sexuality and the Body in the work of six African Women Artists, Wiels, Brussel, 14 februari tot 3 mei 2015
boek